Robotic-assisted laparoscopic management of mesenteric cysts in children - Chen, Qingjiang; Zhang, Shuhao; Luo, Wenjuan; Cai, Duote; Zhang, Yuebin; Huang, Zongwei; Xuan, Xiaoxiao; Xiong, Qixing; Gao, Zhigang (Frontiers in Pediatrics, 2023)
Background Mesenteric cysts (MCs) are rare intra-abdominal masses in children, and laparoscopic complete cyst resection is still difficult. This study reviewed our experience in diagnosing and managing MCs at our center, focusing on the clinical characteristics of MCs and the effectiveness of robotic-assisted laparoscopic surgery. Methods We conducted a retrospective analysis of the records of all patients diagnosed with MCs and managed with robotic-assisted laparoscopic surgery at our center between February 2021 and August 2022. We analyzed demographic characteristics, clinical manifestations, preoperative imaging data, surgical methods, postoperative complications, and final outcomes. Results Totally, 12 consecutive patients with a mean age of 5.81 ± 3.02 years were admitted. The most common symptom was abdominal pain (58.33%). Eight patients were associated with cyst complications, including five cases of infection, two cases of volvulus, and one case of hemorrhage. The mean size of cysts was 8.39 ± 5.91 cm. The cysts were located in ileal mesentery in eight cases, lesser curvature of the stomach in two cases, and colon mesentery in two cases. Solely cyst excision was performed in eight cases, and bowel en bloc resection of the cyst in four cases. Robotic-assisted laparoscopic surgery was performed successfully in all patients, without conversion. The mean operation time was 106.17 ± 33.74 min. Pathological results reported lymphangioma or lymphatic malformation in all patients. Two cases of chylous leakage were treated conservatively, and no complications of peritoneal infection, anastomotic leakage, and recurrence were observed. Conclusions Mesenteric cysts should be removed promptly once the diagnosis is confirmed to avoid cyst complications. For uncomplicated mesenteric cysts, laparoscopic cyst excision, or cyst excision with bowel resection can be effectively performed in children, especially under the robot system.